The ethnomedicine of the Batak Karo people of Merdeka sub-district, North Sumatra, Indonesia - Purba, Endang; -, Nisyawati; Silalahi, Marina (International Journal of Biological Research, 2016)
Background: Ethnomedicine can serve as a platform for studying specific relationships between indigenous cultures and using medicinal plants, thus to identify new chemical compounds used as drugs.Objective: To document the medicinal plants and traditional medicines used by Batak Karo people and to provide information on the pharmacological properties of the most commonly used plants in the preparation to treat of various ailments especially preventive healthcare.Methods: The ethnobotanical study was conducted in Merdeka sub-district, Karo regency, North Sumatra, Indonesia. An intensive field survey was conducted to collect information on medicinal plants used by the people. Data was collected applying semi-structured interviews (individual and group discussions) and questionnaires.Results: A total of 124 plants species have been documented to treat various diseases. Zingiberaceae is the highest number of species being used as traditional medicines especially concoction of preventive healthcare. The study revealed that fever is treated using the highest number of different medicinal species (23 species).Conclusion: Batak Karo people in Merdeka sub-district have a rich local knowledge about medicinal plants. It is a need to extend the documentation of medicinal plants in the area and evaluation its biological activity as a basis for developing future medicines.